Analisis kinerja Jalan Sawunggaling Taman Sidoarjo - Agustya, Muhammad Maulana; Hartatik, Nurani (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The Sawunggaling Highway is classified as a secondary local road and is also a connecting road between provinces. The length of the Sawunggaling road is 2 km with a road width of ± 8 meters and has a 2 (two) Lane 2 (two) Direction (2/2 UD) road type. This research was conducted to determine the traffic volume because traffic jams often occur on Jalan Sawunggaling Taman Sidoarjo. The cause of traffic jams is the large and small number of vehicles crossing the middle of the lane causing road capacity to decrease. The traffic flow on Jalan Raya Sawunggaling is dominated by motorbikes and large trucks, as well as the irregular behavior of motorcyclists which can also reduce the optimal capacity of the road. So it is necessary to analyze traffic volume using Manual Count on this road section. This research method is quantitative using the Road Capacity Manual (MKJI, 1997). The data obtained comes from primary data, Primary data is data from traffic surveys that have been carried out in the field on Jalan Sawunggaling Taman Sidoarjo. The findings of the survey which was carried out from Monday 23 September 2024 to Sunday 29 September 2024, based on this table, the estimated volume of vehicles passing by can be understood if at 17.00 - 18.00 on Friday 27 September 2024 it can be concluded that the number of vehicles is the highest. 2225.45 Curr/hour.